Fiscal risk and its drivers: An empirical analysis - Ugo Panizza (Graduate Institute of International and Development Studies, 2020)
This paper describes and quantifies fiscal risk in advanced and developing economies. Forecast errors in GDP growth explain nearly half of fiscal risk in advanced economies. However, errors in growth forecasts are less important in explaining fiscal risk in low- and middle-income countries. Most of the forecast errors in the debt-to-GDP ratio cannot be explained with standard debt-dynamics variables and needs to be attributed to the "the unexplained part of debt". Fiscal risk is high in bad-times, even when they are fully anticipated. In developing and emerging market economies this result is linked to negative balance sheet effects associated with foreign currency debt. The main drivers of fiscal risk in ADB borrowing countries are exchange rate volatility, commodity prices and small economic size.
Keywords: H61; H62; H63; H68; C82; 330; Fiscal policy; Public debt; Fiscal sustainability